2019
DOI: 10.1159/000494133
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus Colonization in Late Pregnancy and Invasive Infection in Neonates in China: A Population-Based 3-Year Study

Abstract: Background: As no population-based studies of group B Streptococcus (GBS) colonization rates in late pregnancy (at 35–37 weeks of gestation) have been conducted in China, the incidence of and risk factors for neonatal early-onset GBS disease (GBS-EOD) in China remains poorly understood. Objectives: To determine the GBS colonization rate in late pregnancy and neonatal GBS infection in Xiamen, China, and to assess the effectiveness of intrapartum antibiotic prophylaxis (IAP) for the prevention of neonatal GBS-EO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
5
19
0
2
Order By: Relevance
“…The prevalence rates of GBS colonization vary in different geographical regions across the globe. This study showed similar results to those of other studies in Saudi Arabia [ 26 ], Tunisia [ 27 ], and China [ 28 ]. However, studies from Kuwait [ 29 ], Morocco [ 30 ], Iran [ 31 ], Turkey [ 32 ], and Ethiopia [ 33 ] reported higher prevalence rates than those found in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence rates of GBS colonization vary in different geographical regions across the globe. This study showed similar results to those of other studies in Saudi Arabia [ 26 ], Tunisia [ 27 ], and China [ 28 ]. However, studies from Kuwait [ 29 ], Morocco [ 30 ], Iran [ 31 ], Turkey [ 32 ], and Ethiopia [ 33 ] reported higher prevalence rates than those found in this study.…”
Section: Discussionsupporting
confidence: 92%
“…En el presente estudio la frecuencia de colonización (4.3%) fue menor que la reportada en el mundo (17.9%, intervalo de confianza del 95% [IC 95%]: 16.2-19.7%) 22 , con un rango del 11.1% (IC 95%: 6.8-15.3%) en el sudeste asiático al 22.4% en África (IC 95%: 18.1-26.7%). Algunos países como Brasil (14%), China (14%), Nigeria (19.5%) y Arabia Saudita (19%) tienen una frecuencia alta [22][23][24][25][26][27] . En México también hay diferencias con estudios previos realizados: Collado, et al en 1981 encontraron un 4% de colonización 10 , sin embargo, en un centro de atención de tercer nivel en la CDMX se reportó un 10.3%, en una población rural del sur del país encontraron un 8.6% 12 y en un hospital de segundo nivel en el occidente de México un 13% 13 .…”
Section: Discussionunclassified
“…Quizá las diferencias el presente estudio podría explicarse por el tamaño de muestra y que el muestreo fue en mujeres embarazadas que estaban en TP, recién ingresadas y la mayoría con embarazos a término. La colonización por SGB fue mayor en mujeres con embarazo de alto riesgo, esta frecuencia aumenta a mayor edad, sin embargo, esta frecuencia es menor que la observada en otras poblaciones del mundo [22][23][24][25][26][27] .…”
Section: Discussionunclassified
“…27 A GBS-EOD incidence rate of 1.48 per 1000 live births was reported in Xiamen, Fujian Province, which was higher than other regions of China. 28 On the basis of the composition of capsular polysaccharide (CPS), GBS isolates can be divided into ten CPS serotypes (Ia, Ib, and II-IX). A meta-analysis on the serotype distribution of maternal GBS colonization showed that serotype III, the most prevalent, accounted for 25% of serotypes globally.…”
Section: Epidemiology Of Perinatal Gbs Infection In Mainland Chinamentioning
confidence: 99%